Kompetensi Guru pada Penerapan Teknologi Pendidikan di Sekolah - Vinsensius Nase (STIPAS St. Sirilus Ruteng, 2021)
The title of this writing is teacher’s competence on the educationaltechnology application in the school. The aim of this writing is to describethe implementation of educational technology is school to spur and totrigger the learning and instruction in classroom. competence is qualityof performance of teacher. the Teacher is the man who stands in front ofthe class and to teach the students in the class. Application of educationaltechnology need the competence of the teacher or operator of classespecially during the pandemic covid nineteen which struck around theworld. The presence and the existence of educational technology is thebest choice for doing learning and instructional work in school. Duringpandemic covid nineteen, Learning and instruction is no more directedin the school as usually or normal situation but during the pandemiccovid learning and instruction is talked on by media technology like bycellphone, using zoom application, zoom class application, google classapplication, teleconference class application, long distance learning andinstruction application, virtual class application and by homeschooling.A school at home. The use of those applications need skill or competenceof the teacher.The main contribution of educational technology is tofacilitate the student for learning and instruction besides to spur, andto trigger learning and instruction activities of the students.